Nurses’ Perspectives on the Challenges Hindering the Implementation of the Nursing Process: A Qualitative Study - Razzaq Kadhim, Hawraa; Saadi Mohammd, Shatha (Journal of Neonatal Surgery, 2025)
Globally, the cornerstone of the nursing profession is the nursing process (NP). It is considered a scientific method accepted worldwide to guide procedures and provide the best quality of dynamic nursing care. Despite the benefits of the nursing process and the efforts of nursing professionals to implement it, the use of the nursing process is still lagging in most hospitals. This study aims to explore the difficulties that nurses face while putting the nursing process into practice. The study was conducted in the Al-Najaf Al-Ashraf Health Directorate across five teaching hospitals: Al-Zahraa Hospital, Al-Furat Al-Awsat Hospital, Al-Sadder Hospital, Al-Hakim Hospital, and Al-Najaf Hospital. A purposive sample of 12 nurses was selected, most of whom hold a Baccalaureate degree in Nursing with experience ranging from 3 to 15 years. The findings from the qualitative approach reveal several challenges. These include workload difficulties, such as lengthy work hours and extra tasks that are not part of a nurse's duties, as well as a lack of knowledge and training directly relevant to the nursing process. Additionally, there is a shortage of material and human resources. Other significant factors include the absence of incentives, such as poor pay, lack of professional autonomy, and insufficient support from colleagues or management. The lack of clear job descriptions, poor supervision, and the disconnect between what nurses learn in school and the realities of the hospital healthcare system were also identified as major issues. Five themes emerged from the participants' perspectives on the challenges hindering the implementation of the Nursing Process: Professional Growth and Training, Overwhelming Workload, Insufficient Resources, Lack of Encouragement, and Management Support.